Skin-only versus skin-plus-orbicularis resection blepharoplasty: an elaborated analysis of early- and long-term effects on corneal nerves, meibomian glands, dry eye parameters, and eyebrow position - DERİCİOĞLU, VOLKAN; ŞAN, BURÇİN; SEVİK, MEHMET ORKUN; AKKAYA TURHAN, SEMRA (My University, 2023)
Purpose: To evaluate the early- and long-term effects of 2 different blepharoplasty techniques on corneal nerves, meibomian gland morphology, clinical parameters of dry eye disease (DED), and eyebrow position. Methods: This prospective, interventional study included age-sex-matched blepharoplasty patients who had a skin-only resection (24 eyes of 12 patients; Group-S) or a skin-plus-orbicularis muscle resection (24 eyes of 12 patients; Group-M) procedure. Preoperative and postoperative parameters of in vivo corneal confocal microscopy (IVCCM; corneal nerve fiber density [CNFD], nerve branch density [CNBD], and nerve fiber length), meibomian gland area loss (MGAL), DED (Schirmer I test and noninvasive tear breakup time), and eyebrow heights (lateral [LBH] and central [CBH]) were evaluated and compared between the intervention groups (ClinicalTrials.gov, NCT05528016). Results: Compared with baseline, the CNBD of Group-S (19.91 ± 7.66 vs. 16.05 ± 7.28 branches/mm2, p = 0.049) and CNFD of Group-M (19.52 ± 7.45 vs. 16.80 ± 6.95 fibers/mm2, p = 0.028) was significantly decreased at postoperative first week. However, in both groups, IVCCM parameters returned to baseline values at postoperative first month and first year (p > 0.05). A significant MGAL increase was observed in Group-S (18.47 ± 5.43 vs. 19.94 ± 5.31, p = 0.030) and Group-M (18.86 ± 7.06 vs. 20.12 ± 7.01, p = 0.023) at the postoperative first year, demonstrating meibomian gland atrophy. Only significant changes were observed in Group-M in LBH (16.17 ± 2.45 vs. 16.67 ± 2.28 mm, p = 0.044) and CBH (17.33 ± 2.35 vs. 17.96 ± 2.31 mm, p = 0.004) at postoperative first year. Conclusions: Blepharoplasty with or without orbicularis resection seems to have similar effects on IVCCM, DED, and MGAL parameters. However, incorporating an orbicularis muscle resection in a blepharoplasty operation could slightly elevate the eyebrow position.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Göz Hastalıkları ve Cerrahisi; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Eye Diseases and Surgery; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; GÖZ HASTALIKLARI; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; OPHTHALMOLOGY; Cerrahi; Oftalmoloji; Surgery; Ophthalmology